Tubulobulbar complex: Cytoskeletal remodeling to release spermatozoa - Upadhyay Rahul D; Kumar Anita V; Ganeshan Malti; Balasinor Nafisa H (BMC, 2012)
Abstract Tubulobulbar complexes (TBCs) are actin-based structures that help establish close contact between Sertoli-Sertoli cells or Sertoli-mature germ cells (spermatids) in the seminiferous tubules of the testes. They are actin-rich push-through devices that eliminate excess spermatid cytoplasm and prepare mature spermatids for release into the tubular lumen. Just prior to spermiation, the elongated spermatid interacts with the Sertoli cell via an extensive structure comprising various adhesion molecules called the apical ectoplasmic specialization which is partially replaced by the apical TBC, on the concave surface of the spermatid head. The sperm release process involves extensive restructuring, namely the disassembly and reassembly of junctions at the Sertoli-spermatid interface in the seminiferous epithelium. Based on the presence of different classes of molecules in the TBCs or the defects observed in the absence of TBCs, the main functions attributed to TBCs are elimination of excess spermatid cytoplasm, endocytosis and recycling of junctional molecules, shaping of the spermatid acrosome, and forming transient anchoring devices for mature spermatids before they are released. This review summarizes the recent findings that focus on the role of TBCs in cell cytoskeleton restructuring during sperm release in the testes and the molecular mechanism involved.